An Unprecedented Cyano-Induced Sodium Nitrite-Catalyzed C(sp3)-H and C(sp2)-H Coupling Reaction - Li, Ling; Su, Bo; Liu, Yuxiu; Wang, Qingmin (Current Organic Synthesis, 2018)
Aim and Objective: During the investigation of sodium nitrite-catalyzed oxidative coupling reaction of aryls, an unprecedented C(sp2)-H and C(sp3)-H coupling of substituted 2-aryl acetonitrile was found. Materials and Methods: The structure of the coupled product was confirmed by 1H and 13C NMR spectroscopy and high-resolution mass spectrometry (HRMS), and comparison of its derivatives with known compounds. The effects of methoxy group in the benzene ring on the reaction were evaluated. Results: The optimized reaction conditions are summarized as follows: CF3SO3H/substrate = 1.5 equiv., NaNO2/substrate = 0.3 equiv., CH3CN as solvent. 2-(4-Methoxyphenyl)acetonitrile and 2-(3,4,5- trimethoxyphenyl)acetonitrile could also generate C(sp2)-H and C(sp3)-H coupling. The coupling reaction occurred as a typical radial mechanism. Conclusion: An unprecedented cyano-induced, NaNO2-catalyzed oxidative C(sp3)-H and C(sp2)-H coupling was reported. The reaction proceeded under very mild conditions, using O2 in the air as terminal oxidant. The unique oxidative manner might provide more inspiration for the development of intriguing oxidative coupling reactions.
Keywords: Coupling reaction